Nondestructive Investigation of Stress-Induced Damage in Concrete - P. Shokouhi; A. Zoëga; H. Wiggenhauser (Advances in Civil Engineering)
The changes in the sonic surface wave velocity of concrete under stress were investigated in this paper. Surface wave velocities at sonic frequency range were measured on a prismatic concrete specimen undergoing several cycles of uniaxial compression. The loading was applied (or removed) gradually in predefined small steps (stress-controlled). The surface wave velocity was measured at every load step during both loading and unloading phases. Acoustic Emission (AE) test was conducted simultaneously to monitor the microcracking activities at different levels of loading. It was found that the sonic surface wave velocity is highly stress dependent and the velocity-stress relationship follows a particular trend. The observed trend could be explained by a combination of acoustoelasticity and microcracking theories, each valid over a certain range of applied stresses. Having measured the velocities while unloading, when the material suffers no further damage, the effect of stress and damage could be differentiated. The slope of the velocity-stress curves over the elastic region was calculated for different load cycles. This quantity was normalized to yield a dimensionless nonlinear parameter. This parameter generally increases with the level of induced damage in concrete.